Plasma filaments in the scrape-off layer of Wendelstein 7-X. (22nd June 2020) - Killer, Carsten; Shanahan, Brendan; Grulke, Olaf; Endler, Michael; Hammond, Kenneth; Rudischhauser, Lukas
Abstract: Plasma filaments have been observed by reciprocating electric probes in the Scrape-Off Layer (SOL) of the Wendelstein 7-X stellarator. Comparison with target probes indicates that a filament observed in the W7-X SOL extends to the sheath. Two-dimensional simulations of seeded filaments exhibit good quantitative agreement with experimental measurements in filament velocity scalings, despite an assumption of constant field line curvature. Both experiment and simulation show a slow radial propagation of filaments, indicating that filaments are essentially bound to their flux surface and do not perform ballistic radial motion. In contrast, the poloidal propagation along flux surfaces is much faster than the radial motion.